Angiographic SYNTAX score reduction in de novo left main coronary stenosis patients over the last decade: implications for revascularization approach. (25th November 2020) - Chmiel, J; Ksiazek, M.K; Dradrach, J; Wnuk, G; Malinowski, K.P; Iwaszczuk, P; Podolec, P; Musialek, P
Abstract: Introduction: Percutaneous management of left main (LM) coronary artery stenosis is an acceptable alternative to surgery in selected group of patients. Purpose: To investigate potential angiographic trends in de novo LM coronary artery stenosis patients. Those may impact revascularization mode but remain undetermined. Methods: Clinical records and all consecutive coronary angiograms in our Institution from 1st January 2010 to 31stDecember 2019 were evaluated to identify those with newly diagnosed angiography-significant (≥50% lumen diameter reduction) LM stenosis. Angiographic SYNTAX score (SS) assessment was performed by agreement of two experienced analysts (an angiographic core lab analyst and a Heart Team interventional cardiologist) on anonymized angiograms. Values of the overall SS, SS of the LM lesion and SS beyond LM were determined according to SS assessment methodology. Pearson's correlation and Fisher transformation were used to evaluate parametric variables. Spearman's rho was used to determine trends. Results: Overall, out of 12315 coronary angiographies performed in de novo referrals in the last decade, 357 (2.90%) showed significant left main stenosis; the proportion varied from 2.30% to 3.48% annually. Patient mean age was 68.8 years (23.3% women). No temporal trends in patient age or gender occurred over the last decade while the overall SS deceased from a mean value of 35 to 28 (SC=−0.16, p=0.003). Further analysis showed a particular negative trend in the non-LM-SS (SC=−0.17, p=0.001) but not in the LM-SS (SC=0.04, p=0.47). No temporal trend was present is the prevalence of isolated LM stenosis (p=0.48) and no temporal trend in the LM stenosis angiographic severity (<70% vs. ≥70%; p=0.61), LM stenosis location (ostial/mid/bifurcation/entire left main; p=0.30) nor in the number of LM segments affected (SC=0.05, p=0.30). Reduction in the non-LM-SS was associated with a decrease in the number of coronary arteries with a significant angiographic atherosclerotic involvement (SC=−0.12, p=0.03) and in the number of coexisting total occlusions (SC=−0.25, p<0.001). Conclusion(s): (1) In patients with newly diagnosed LM critical stenosis overall angiographic SS showed a statistically significant negative trend over last decade, with a reduction from mean 35 (2010) to 28 points (2019); a finding that may be related to a change in the angiographic presentation of the disease or an earlier identification of LM stenosis patients over time. (2) The overall SS reduction was driven by a decrease in non-LM-SS. This, taken together with the overall SS reduction from above 32 to below 32, favours (as per current guidelines) the endovascular approach to left main revascularization. Our findings suggest an increase in the proportion of LM stenosis patients with angiography feasible to percutaneous intervention. Funding Acknowledgement: Type of funding source: None